Grožinės verstinės vaikų knygos leidyba Lietuvoje 1940- 1990 m. - Mozūraitė, Vita (Knygotyra, 2024)
Translated literature comprises a significant portion of all children's books in Lithuania. Often, works originally written for adults become popular as children's literature worldwide (e.g., D. Defoe's, J. Swift's, A. Dumas', Ch. Perrault's, and others). As a result, many book editors face difficulties in determining the appropriate target audience for these books. Consequently, the same classic literary work, published in Lithuania at different times, may be aimed at various reader groups (for example, "Robinson Crusoe").Fiction has always constituted the largest portion of children's books in Lithuania (in some years, up to 93%). Translations made up 54.7% of all children's fiction published from 1940 until 1990. The majority of these books are prose and are primarily aimed at younger and middle-school-age readers (65.9%), with the smallest portion targeted at older school-age readers (15.9%). Poetry accounts for 11% of all children's book translations, with the majority of it intended for younger readers.Between 1940 and 1990, 1881 translated fiction books for children were published in Lithuania. These books were translated from 29 languages representing 88 nations worldwide by more than 800 translators. The majority of these books were translated from Russian (about 45%). The literary and folklore books of various nations within the U.S.S.R. comprise 60.7% of all children's translations. Of these, 79.7% were by Russian creators, while the remaining 20.3% were by creators from 31 other nations within the U.S.S.R.There were many challenges associated with translations, most of which were dictated by central departments in Moscow that regulated all publishing activities in the Soviet Union.